Spatial Variability of the Bioclimatic Conditions of the Roztocze National Park Based on the Example of the Cycling Path to Florianka - Marta Ziółek; Marcin Kozieł; Paweł Czubla (Barometr Regionalny, 2015)
The Roztocze National Park (RNP) is a typical forest park – 94% of its area is occupied by forest. A total of 13 forest communities are distinguished within RNP. The most valuable ones are Carpathian beech forest and uplands mixed fir coniferous forest, occupying almost 34% of the forested area of RNP. The microclimatic conditions occurring in forests differ considerably from those occurring in non-forested areas. Forests absorb dust and gas pollutants, suppress noise, and enrich the air in aromatic substances. The climate of the forest interior depends on aspects such as the species composition of the forest, density of crown trees, and habitat properties. Therefore, the effect of various forest communities on the human organism is different. This paper describes the forest communities appearing in RNP pointing out their therapeutic values, with particular consideration of the cycling path “to Florianka” (“do Florianki”). Based on GIS software, a spatial analysis of the properties of particular forest communities was performed. Maps were prepared presenting the bioclimate of the recreational layer of the forests, including: insulation, ventilation, humidity, oxygen and ozone production, ionisation, and content of aeroplankton and phytoaerosoles. The bioclimate occurring in particular communities was assessed as favourable/neutral/unfavourable for the human organism. The attractiveness of its environment makes RNP very popular among tourists (>100 thousand annually ). Tourist and didactic trails are established in the Park, with a total length of approximately 40 km. They run near the most interesting environmental, cultural, and historical objects. An example of such a trail is the cycling path “to Florianka” that was the subject of the detailed analysis. It has a length of approximately 10 km and is the longest trail established in RNP. The trail features the highest diversity of forest communities distinguished by a favourable effect on the human organism.